2021
DOI: 10.3389/fimmu.2020.608686
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Fasciola hepatica miRnome Predicts a Targeted Regulation of Mammalian Innate Immune Responses

Abstract: Understanding mechanisms by which parasitic worms (helminths) control their hosts’ immune responses is critical to the development of effective new disease interventions. Fasciola hepatica, a global scourge of humans and their livestock, suppresses host innate immune responses within hours of infection, ensuring that host protective responses are quickly incapacitated. This allows the parasite to freely migrate from the intestine, through the liver to ultimately reside in the bile duct, where the parasite esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 68 publications
(75 reference statements)
1
27
0
Order By: Relevance
“…Note that the total of 89 sequences considers 5p and 3p sequences from the same hairpin as separate mature sequences. Note that after we completed this part of the study in 2020, a similar analysis was published by other authors (Ricafrente et al, 2020).…”
Section: Redundancy and Diversity Within Published F Hepatica Mirna Datasetsmentioning
confidence: 59%
See 3 more Smart Citations
“…Note that the total of 89 sequences considers 5p and 3p sequences from the same hairpin as separate mature sequences. Note that after we completed this part of the study in 2020, a similar analysis was published by other authors (Ricafrente et al, 2020).…”
Section: Redundancy and Diversity Within Published F Hepatica Mirna Datasetsmentioning
confidence: 59%
“…Ovchinnikov et al focused on adult EV miRNAs, uding PITA and TargetSCAN to link 24 miRNAs to 321 cow and human mRNAs, including targets within the Wnt signalling pathway and the immune system (Ovchinnikov et al, 2020). Similarly, (Ricafrente et al, 2020) used miRTarget to link 38 NEJ expressed miRNAs (Fontenla et al, 2015a) with 26 target genes expressed in innate immune cells. Our work builds on previous studies to catalogue new miRNAs within an expanded F. hepatica miRNome, alongside a developmental expression profile of these in muiltiple intramammalian life stages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is comparable to the in vitro apoptotic effects of the ES proteins on peritoneal eosinophils and macrophages [ 222–224 ]. Furthermore, transcriptional analysis revealed that pro-apoptotic signals are increased in peripheral blood mononuclear cells recovered from F. hepatica infected sheep and cattle [ 225 , 226 ]. The specific proteins that bring about this cellular apoptosis have yet to be characterized, and further studies are required to determine whether similar parasite proteins are involved within the different immune compartments of the infected animal.…”
Section: Mechanisms Of Pathogenicity Of Fasciola Spp Parasitesmentioning
confidence: 99%